Syntactical Pattern of News Headlines in The Jakarta Post and The Diplomat Reporting The 2024 Indonesian Presidential Election - Panji, Artha Nur Restia; Kadir, Puspa Mirani; Wagiati, Wagiati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The research discussed the syntactical pattern in news headlines between two different-country background news report channels, The Jakarta Post and The Diplomat reporting the same case, that was Indonesian Election 2024. The data source consists of twenty different news titles from both channels published on June 6, 2023. A qualitative approach with a descriptive analysis is used in this research. The Syntax underlying tree pattern by Van Valin et al (1997) serves as the framework for this research. The research findings showed that it was found that the Indonesian channel, Jakarta Post, have all sentential headline pattern in their ten news with nine simple sentences and one complex sentence, while The Diplomat which is from America, have eight sentential headlines and two phrased pattern from their ten news with simple sentence form at all headlines.